(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
The objective of this study was to determine the effects of improvedmanagement and nutrition on the reproductive performance of a flock of Tagger goatsfrom Eldaleng area, the Nuba Mountains. It was conducted at Wad Medani , Sudan, fromJune 2006 to July 2008. The goats were mainly grazed on farm and well managed.Individual records were kept for each animal, and the data were statistically analysed forreproductive characteristics. Kidding percentage was 100% in the two years and wasmainly in summer. Sex ratio (males to females) was 57.14: 42.86 in the first year and54.05: 45.95 in the second year. Twinning rate increased from 17.39% in the first year to48.0% in the second year, and number of kids born /doe increased from 1.17 in the firstyear to 1.48 in the second year. Mean age at first kidding was 365.67 days (285- 438)and mean kidding interval was 258.85 days (169- 380). The overall birth weight was1.73, 1.69 and 1.70 kg for the first, second and third parities, respectively. Seasons hadno significant effects on overall birth weight, and it was highest in summer (1.74)followed by autumn (1.71) and then winter (1.63).There were differences between yearsin birth weight and was generally higher in the first year. Singles were heavier at birththan twins. Birth weight had a significant correlation with doe weight at kidding. Doeage had significant correlations with doe body condition score and doe weight atkidding. The results showed that Tagger reproductive performance was improved in theGezira area, especially in the second year, than in Eldaleng area.